HISTOPATHOLOGICAL CHANGES IN VISCERAL SCHISTOSOMOSIS CAUSED BY Schistosoma spindale IN CATTLE - Shivani Mamane; N. Jeyathilakan; Bhaskaran Ravi Latha; T.M.A. Senthilkumar; N. Pazhanivel (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Bovine visceral schistosomosis is an important economic, chronic wasting blood fluke illness caused primarily by Schistosoma spindale. The abattoir samples of mesenteric veins, mesenteric lymph nodes and mesenteric fat of S. spindale infected cattle were subjected to histopathological studies. Microscopically it was observed that the mesenteric veins had a cross section of Schistosoma spindale adult worms with mild intimal proliferation and slight thickening of tunica media layer. Mesenteric lymph node revealed mild lymphoid cell depletion and thickening of the medullary trabeculae. The macrophage laden with hemosiderin pigment in cortical and paracortical area of lymph node was confirmed by Perl’s Prussian blue staining. Fat necrosis with mononuclear cell infiltration and venous thrombosis were also observed in the mesenteric fat.